Entrecruzamento de trajetórias : autobiografias de Maria Firmina Dos Reis e Nísia Floresta como ancoragem para o ensino de história - Elias, Beatriz Berr (2024)
In this master's research, an autobiographical journey of the author with feminist hermeneutical studies in the works of Nísia Floresta, "Itinerary of a Journey to Germany" (1857), and Maria Firmina dos Reis, "Album" (1853 - 1901), is presented. The research question seeks to understand how the autobiographical writing of these two authors can serve as a conscious anchor for this type of knowledge in the contexto of emancipatory History education. These two autobiographical texts prompted a reflection on the concept of anchoring as a driving force for a more inclusive History education. The female authorship of the studied authors and the master's student also enabled a reflection on the democratization of women's works that make their way (or don't make their way) into the classroom for study